2017
DOI: 10.1161/circoutcomes.116.003132
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Implementation of Practice Standards for Electrocardiographic Monitoring With Nurses’ Knowledge, Quality of Care, and Patient Outcomes

Abstract: Background Although continuous electrocardiographic (ECG) monitoring is ubiquitous in hospitals, monitoring practices are inconsistent. We evaluated implementation of American Heart Association practice standards for ECG monitoring on nurses’ knowledge, quality of care, and patient outcomes. Methods and Results The PULSE Trial was a 6-year multi-site randomized clinical trial with crossover that took place in 65 cardiac units in 17 hospitals. We measured outcomes at baseline, Time 2 after Group 1 hospitals r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 30 publications
1
51
0
4
Order By: Relevance
“…27 Continuing education and training in monitor use can both enhance the knowledge and competence of nurses in patient surveillance and improve patient outcoms. 28 This can be achieved by implementing a core curriculum for the continuing professional education for qualified cardiac nurses, including learning activities in the role of technology in patient safety, heart rhythm, conduction disorders and EKG skills. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Continuing education and training in monitor use can both enhance the knowledge and competence of nurses in patient surveillance and improve patient outcoms. 28 This can be achieved by implementing a core curriculum for the continuing professional education for qualified cardiac nurses, including learning activities in the role of technology in patient safety, heart rhythm, conduction disorders and EKG skills. 29…”
Section: Discussionmentioning
confidence: 99%
“…1 Implementing protocols for appropriate monitor use, educating nurses in monitoring practice standards and involving them in the monitor discontinuation decision process can potentially eliminate monitor overuse and reduce excessive nuisance alarms. 28 The nurses observed in this study were mobile in their work and nursing tasks took them all over the unit, and even outside of it, to care for their patients. Considered alongside the layout of the unit, this made it difficult for them to hear and respond to the alarms effectively, which has been shown to affect alarm safety.…”
Section: Work Methods and Environmentmentioning
confidence: 99%
“…The PULSE trial, a 6- year multisite randomized controlled trial, examined the effects of implementing the 2004 AHA standards for ECG monitoring on nurses' knowledge, quality of care, and patient outcomes. 4 The study revealed that improving nurses' knowledge about appropriate ECG monitoring leads to better patient outcomes. Dr Funk reminded the audience that an Update to the Practice Standards for Electrocardiographic Monitoring in Hospital Settings was published recently in Circulation.…”
Section: Ecg Monitoringmentioning
confidence: 98%
“…Dr Marjorie Funk presented the findings from the PULSE (Practical Use of the Latest Standards for Electrocardiography) trial. The PULSE trial, a 6‐year multisite randomized controlled trial, examined the effects of implementing the 2004 AHA standards for ECG monitoring on nurses’ knowledge, quality of care, and patient outcomes 4. The study revealed that improving nurses’ knowledge about appropriate ECG monitoring leads to better patient outcomes.…”
Section: Ecg Monitoringmentioning
confidence: 99%
“…Nurses should have enough knowledge to carry out these responsibilities so that they can maximize the quality of care and patient outcomes. [6] Nurses should be able to quickly and correctly detect and interpret ECG abnormalities and intervene in a timely manner. [7]…”
Section: Introductionmentioning
confidence: 99%